Impact of face masks on empathy and communication in head and neck cancer patients: a case-control study - Hoene, Georg; von Hahn, Nikolaus; Mathea, Tim; Schminke, Boris; Goldstein, Kathi; Leu, Martin; Schliephake, Henning; Wolfer, Susanne (Frontiers in Oncology, 2025)
BackgroundThe COVID-19 pandemic necessitated the widespread use of face masks in medical settings. In the treatment of patients with head and neck tumors or other malignancies, where non-verbal communication and emotional expression are critical, face masks may potentially impair the physician-patient relationship. This study aimed to assess the impact of face masks on perceived empathy and the quality of physician-patient communication in this patient cohort.MethodsA prospective case-control study as part of the postoperative follow-up consultations was conducted at the Department of Oral and Maxillofacial Surgery, University Medical Center Goettingen, utilizing the Consultation and Relational Empathy (CARE) measure. Patients were divided into two groups: in the case group, clinicians wore face masks throughout the entire consultation, while in the control group, masks were worn only during the clinical examination. The primary outcome was the difference in CARE scores, reflecting the perceived empathy of the clinician.ResultsNo significant difference in mean CARE scores was observed between the two groups (p=0.454), indicating that wearing a face mask did not significantly affect patients’ perception of clinician empathy. However, a significant positive correlation was found between patients’ familiarity with the clinician and higher CARE scores (p=0.003). Other variables, such as patient health status and consultation duration, did not significantly influence CARE scores.ConclusionWearing face masks does not significantly impair perceived empathy in the context of physician-patient communication. Familiarity with the clinician emerged as a key factor in enhancing the quality of the interaction. These findings underscore the importance of fostering long-term, trust-based physician-patient relationships, particularly during periods of pandemic-related protective measures such as mask mandates.